CREATION AND USE OF INDEPENDENT ASSIGNMENTS IN THE ORGANIZATION AND TEACHING OF PRIMARY TRAINING FOR THE MODULE-CREDIT SYSTEM - Abdullayev Mustafo Qalandar o‘g‘li (Journals Park Publishing, 2023)
Current status and prospects of transition to the credit-module system in the development of independent educational tasks of students in the organization of primary training before the convocation, credit-module based on advanced world experiences of higher education institutions system principles, learner, recognition of educational results. It is desirable to create the possibility of independent formation of the educational trajectory and academic mobility, the accumulation of grades, the interest of professors and students in the organization and teaching of primary training before the convocation, as well as the introduction of a clearly defined evaluation system it is justified.
Keywords: methodology, pedagogical features, higher education, pre-vocational primary training, organization, teaching methodology, modern teaching requirements, educational tasks, speech competence.